Innovative mucosal flaps for post-operative pain relief in endoscopic assisted tonsillectomy - Munjal, Manish; Munjal, Shubham; Gill, Karambir; Sharma, Salony; Talwar, Shivam; Chawla, Deeksha; Kaur, Hardeep; Sandhu, Loveleen; Gill, Zoya; Kaur, Gursimran; Rishi, Ojassivi; Joshi, Tanvi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Tonsillectomy the “bread and butter” surgery of the Otorhinolaryngologist has graduated from the Gullitone to the state of the art plasma knife technique, vis a vis patient and surgeon comfort. The excruciating post recovery pain is due to breach in the oro-phayngeal mucosa and thereby irritation of the terminal arborizations of the glossopharyngeal and vagal innervations. Moreover, the surgical trauma induced inflammation and spasm of the constrictor muscles leads to ischemia and a protracted cycle of pain. An endoscopic assisted bi -mucosal flap technique with precision and homeostasis is ideal as it covers the raw bed of the tonsil and there thereby reduces the intensity of the postoperative pain.